(untitled) (Research, Society and Development, 2020)
Solid waste generation is directly associated with human activities, whether in rural or urban areas. Poor management of this solid waste results a problem that affects public health and the environment, requiring the development of practical solutions to mitigate its consequences. The objective of this research was to assess the perception of residents of Sítio Estrela community located in the rural area of Barbalha-CE ​​municipality, about the solids waste, well as a generation, disposal, recycle, and the consequences to the environmental and human health. For this purpose, it was carried descriptive research and exploratory type through a semi–structured questionnaire. The results showed that residents commit failures when managing their homes due to a lack of information and awareness about the risks to the population’s health and the environment generated by inadequate disposal of their waste, evidencing the need for the municipality to work on environmental education in these communities.